Intellectual, educational, and behavioural sequelae after cranial irradiation and chemotherapy. Issue 6 (June 1994) - Anderson, V; Smibert, E; Ekert, H; Godber, T
Abstract : Cognitive and educational sequelae are inconsistently reported in children treated with cranial irradiation for acute lymphoblastic leukaemia. This study investigated differences in these skills after cranial irradiation, controlling the effects of chemotherapy and psychosocial factors. Three groups were evaluated: 100 children diagnosed with acute lymphoblastic leukaemia and treated with cranial irradiation and chemotherapy; 50 children diagnosed with acute lymphoblastic leukaemia or other cancers and treated with chemotherapy alone; and a healthy control group of 100 children. Children in the clinical groups stopped treatment at least two years before evaluation and had no history of relapse. Children were aged between 7 and 16 at the time of assessment. Evaluation included cognitive, educational, and behavioural measures. Analyses found that children receiving cranial irradiation and chemotherapy performed more poorly than non-irradiated groups on intellectual and educational tests, with verbal and attentional deficits most pronounced. Children receiving chemotherapy alone performed similarly to controls, suggesting such treatment is not associated with adverse neurobehavioural sequelae.